The Analysis of Students’ Opinions about the Social Responsibility Of Ukrainian Universities - Tryma, Kateryna (Journal of Education Culture and Society, 2021)
Aim. The paper is aimed to investigate the students’ opinion about the social responsibility carried out by higher education institutions (HEIs) in Ukraine. Nowadays social responsibility has become one of the key characteristics of modern HEIs. Ukrainian universities are trying to become 'civic universities', i.e., institutions which contribute to the development of the local community. The students, as key stakeholders of the university activities, also take part in this process. Methods. To investigate the social responsibility of the Ukrainian HEIs, the case study method is used in the present paper: the case of Mariupol State University and its social functions within the city are highlighted. The online survey was applied to investigate the level of students’ awareness of the university social functions and the role played by the university in the local community. Materials published by the university and the results of the survey have been analysed to test the hypothesis that students consider Mariupol State University to be a socially responsible university which cooperates with the local community. Results. The students’ opinion on the social functions carried out by Mariupol State University is that this local university has strong ties with the local community and authorities and perform its social mission. However, the social functions of the university, according to the students, are limited by teaching and research activities. Few students consider social responsibility of the university in a wider context. Conclusion. On the example of the MSU the paper shows that modern universities in Ukraine perform social functions and try to become truly civic universities to contribute to the development of the local communities in cooperation with different stakeholders. Nevertheless, students as a key stakeholder of the university activities still consider social responsibility of the university primarily aimed at teaching and research.